In-situ impregnation method for 3D printing of rock

CN118812250BActive Publication Date: 2026-10-27INST OF ROCK & SOIL MECHANICS CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411095760.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2026-10-27
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

[0005]针对粉末床3D打印技术成形米级岩石试样难以浸渗处理的问题,以及现有浸渗处理工艺无法满足岩石试样不同部位的差异化强度需求和化学成分需求,本发明提供一种岩石3D打印原位浸渗方法,采用粉末床3D打印的方式喷墨打印固化树脂成形单一层后,按试样致密度和矿物成分需求,在同一层内特定区域挤出打印可转变成不同矿物成分的浸渗剂,最终逐层累积形成与天然岩石在强度和矿物成分分布上更为接近的岩石试样

Benefits of technology

[0026]传统浸渗方法是利用浸渗液的浓度差、气压差及毛细现象实现对非致密试样的浸渗,但是对于大尺寸试样随着浸渗深度的增大,仅通过增加浸渗压力或浸渗液浓度已无法有效提升试样浸渗度。本发明采用逐层原位浸渗工艺,同样是基于毛细现象实现对试样的浸渗,但浸渗过程只需发生在新成形的单一层内,这大大降低了对浸渗压力和浸渗浓度的需求。同时通过更换浸渗液,还可以实现试样内部多种浸渗液的可控浸渗。解决了大尺寸、高填充密度的3D打印岩石试样存在的浸渗度不足、浸渗不均匀的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812250B_ABST
    Figure CN118812250B_ABST
Patent Text Reader

Abstract

The application discloses an in-situ impregnation method for rock 3D printing, wherein quartz powder, feldspar powder, rock debris powder, clay powder and a solidifying agent are uniformly mixed according to the proportion of sandstone mineral components; powder bed 3D printing technology is adopted to complete powder laying on a printing surface; an inkjet printing binder is printed on the printing surface according to a three-dimensional geometric model of the sandstone, so as to form a cross-sectional shape of a rock sample; a printing impregnating agent is extruded on the printing surface according to the three-dimensional spatial distribution of the sandstone mineral components, so as to meet the requirements of chemical components and strength of different parts of the rock sample on a single cross section; the in-situ impregnated rock sample is prepared layer by layer; and the rock sample after printing is high-temperature sintered to complete mineralization transformation of the impregnating agent and strength improvement of the sample; according to the sample density and mineral component requirements, the impregnating agent which can be transformed into different mineral components is extruded and printed layer by layer based on the powder bed 3D printing technology, and finally a rock sample which is more close to natural rock in strength and mineral component distribution is formed layer by layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of 3D printing technology, specifically relating to an in-situ infiltration method for 3D printing of rocks. Background Technology

[0002] Sandstone is the most widely used stone material by humans, mainly composed of quartz, feldspar, and rock fragments. The clastic particles in sandstone are cemented together by cementing agents to form a dense and hard blocky structure. Based on the content of the main clastic components, sandstone can be divided into quartz sandstone, feldspar sandstone, and rock fragment sandstone. As a geological material composed of various minerals and structures, rock has a complex mineral composition and an uncontrollable three-dimensional spatial distribution, making it difficult to manufacture rock samples containing specific mineral components with controllable three-dimensional spatial distribution using traditional processing methods. Therefore, developing sandstone manufacturing methods with controllable mineral composition (quartz, feldspar, and rock fragments) and their three-dimensional spatial distribution is of great significance for research on the mechanical characteristics, failure mechanisms, and disaster prevention and mitigation in geotechnical engineering, using sandstone as a representative example.

[0003] Rock 3D printing technology involves printing rock-like materials using 3D printing technology. The main process is as follows: preparing a rock-like printing material; solidifying the rock-like material into a rough block through physical / chemical reactions; and then processing the rough block using post-processing techniques (such as debinding, sintering, and infiltration) to obtain rock specimens. As reported in the literature (Method of fabricating artificial rock specimens based on extrusion freeforming (EFF) 3D printing), rock 3D printing mainly includes extrusion 3D printing technologies (such as melt extrusion molding and inkjet molding) and powder bed 3D printing technologies (such as selective laser sintering and binder jetting). The printing materials are mostly gypsum and its composites; and most of the printed specimens require debinding and sintering post-processing. It can be seen that existing 3D printing technologies for forming rocks suffer from problems such as small specimen size, high organic content, and limited mineral composition.

[0004] For rock samples, powder bed 3D printing is the preferred technology (e.g., CN 116809870 A and CN112028551A). This 3D printing technology uses a binder (such as furan resin, phenolic resin, or epoxy resin) to bond rock powder together to prepare the desired sample. However, due to limitations in the forming principle, the density of the rough blank obtained by direct printing is approximately 1.8 g / cm³. 3With a strength of approximately 3–8 MPa, its performance is insufficient for direct use. Therefore, post-impregnation treatment processes are necessary to improve the density and strength of the samples. However, for large-sized samples, the impregnation depth is often affected by the fluidity of the impregnating agent, its penetration and diffusion capacity, and the porosity of the sample, making complete penetration difficult. Furthermore, when preparing rock samples using 3D printing, different parts of the rock sample have different strength and chemical composition requirements, and existing impregnation processes cannot meet the differentiated impregnation needs of different parts of the same rock sample. Summary of the Invention

[0005] To address the difficulty in impregnating meter-sized rock samples formed by powder bed 3D printing, and the inability of existing impregnation processes to meet the differentiated strength and chemical composition requirements of different parts of the rock sample, this invention provides an in-situ impregnation method for rock 3D printing. After inkjet printing a cured resin to form a single layer using powder bed 3D printing, an impregnating agent that can be transformed into different mineral compositions is extruded and printed in specific areas within the same layer according to the sample density and mineral composition requirements. Finally, layer by layer, a rock sample that is closer to natural rock in terms of strength and mineral composition distribution is formed.

[0006] To achieve the above objectives, the following technical solution is adopted:

[0007] An in-situ infiltration method for 3D printing of rocks includes the following steps:

[0008] (1) Mix quartz powder, feldspar powder, rock fragment powder, clay powder and curing agent evenly according to the proportion of sandstone mineral composition;

[0009] (2) Powder bed 3D printing technology is used to lay powder on the printing surface;

[0010] (3) Based on the three-dimensional geometric model of sandstone, inkjet print the binder on the printing surface to form the cross-sectional shape of the rock sample; based on the three-dimensional spatial distribution of sandstone mineral composition, extrude and print the impregnating agent on the printing surface to meet the requirements of chemical composition and strength of different parts of the rock sample on a single cross section;

[0011] (4) Repeat step (3) to prepare in-situ infiltrated rock samples layer by layer;

[0012] (5) The printed rock sample is sintered at high temperature to complete the mineralization transformation of the impregnating agent and improve the strength of the sample.

[0013] According to the above scheme, the quartz powder mentioned in step 1 is a mixture of large-particle-size powder of 100-200μm and small-particle-size powder of 10-50μm; the mass ratio of the two quartz powders can be 9:1, 8:2, 7:3 or 6:4 according to the powder gradation relationship.

[0014] According to the above scheme, the feldspar powder mentioned in step 1 is any one or a mixture of sodium feldspar, potassium feldspar, and calcium feldspar; the particle size range is 50-200 μm.

[0015] According to the above scheme, the rock fragments powder mentioned in step 1 are igneous rock fragments; the clay powder is kaolinite or hydromica; the particle size range is 2 to 20 μm.

[0016] According to the above scheme, the curing agent in step 1 is toluenesulfonic acid; the amount used accounts for 0.3% to 1% of the total mass of the powder.

[0017] According to the above scheme, step 2 uses vacuum suction powder delivery or powder delivery belt to deliver the mixed powder to the 3D printer; the powder spreading process includes two steps: powder delivery and surface leveling. The powder delivery method is either a bottom powder delivery based on the lifting of the powder delivery cylinder or an top powder delivery based on the powder drop hopper; the surface leveling is achieved by rotating the powder spreading roller or moving the scraper.

[0018] According to the above scheme, the thickness of a single layer of powder in step 2 ranges from 0.05 to 0.4 mm.

[0019] According to the above scheme, in step 3, the inkjet printing adhesive adopts a microdroplet jetting method based on pressure point drive or heat drive; the adhesive is a furan resin solution.

[0020] According to the above scheme, step 3, the extrusion printing of the impregnating agent adopts micro-droplet jetting or liquid extrusion; the impregnating agent is any one or a mixture of silicon-based impregnating agent, silicon-aluminum-based impregnating agent, and aluminum-based impregnating agent, depending on the chemical composition requirements of the rock sample.

[0021] According to the above scheme, the silicon-based impregnating agent is any one of water glass, alkoxysilane, and silica sol.

[0022] According to the above scheme, the silicon-aluminum impregnating agent is a silicon-aluminum gel system; wherein any one or a mixture of water glass and alkoxysilane is used as the silicon source for preparing silicon-aluminum gel; any one or a mixture of aluminum sulfate, aluminum chloride, and aluminum hydroxide is used as the aluminum source for preparing silicon-aluminum gel; the silicon source and aluminum source are blended to obtain the silicon-aluminum impregnating agent.

[0023] According to the above scheme, the aluminum-based impregnating agent is a sol-gel aluminum impregnating agent or a pyrolytic aluminum impregnating agent. Specifically, it is any one of boehmite sol, ammonium aluminum sulfate, ammonium aluminum carbonate, and aluminum chloride.

[0024] According to the above scheme, the temperature for high-temperature sintering in step 5 is 1000–1400℃, and the sintering time is 12–24 hours.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0026] Traditional infiltration methods utilize concentration differences, pressure differences, and capillary action to infiltrate non-dense samples. However, for large-sized samples, increasing the infiltration pressure or concentration alone is insufficient to effectively improve infiltration depth as the infiltration depth increases. This invention employs a layer-by-layer in-situ infiltration process, also based on capillary action, but the infiltration process only occurs within the newly formed single layer, significantly reducing the requirements for infiltration pressure and concentration. Furthermore, by changing the infiltration solution, controlled infiltration with multiple solutions within the sample can be achieved. This solves the problems of insufficient and uneven infiltration in large-sized, high-fill-density 3D-printed rock samples.

[0027] Furthermore, the uncertainty of mineral composition and the non-uniformity of mineral distribution in natural rocks make it difficult for traditional 3D printing technology to form samples with variable material compositions. Existing rock 3D printing technology can only form rock samples with a single component and uniform distribution. The 3D printing layer-by-layer in-situ infiltration forming method proposed in this invention, based on continuous infiltration in local areas within the sample, controls the infiltration composition of different parts of the rock sample by changing the infiltration liquid, thereby adjusting the internal mineral composition of the sample. The resulting rock sample has a controllable internal mineral distribution area and composition, and is closer to natural rocks.

[0028] This invention addresses the issues of insufficient and uneven infiltration in large-sized, high-fill-density 3D-printed rock samples by printing the impregnating agent layer-by-layer in situ during the preparation of rock samples using powder bed 3D printing. Furthermore, by printing the impregnating agent layer-by-layer in situ, the location and quantity of the impregnating agent within the rock sample can be precisely controlled according to requirements, achieving precise control over the strength of different parts of the rock sample. By printing different types of impregnating agents layer-by-layer, the chemical composition of different parts of the rock sample can also be precisely controlled according to requirements, resulting in a higher degree of similarity between the chemical composition distribution of the obtained rock sample and real rock. Attached Figure Description

[0029] Figure 1 : Schematic diagram of the in-situ rock 3D printing infiltration device of the present invention;

[0030] Figure 2 : Schematic diagram of the main components of the in-situ rock 3D printing infiltration device of the present invention;

[0031] Figure 3 : Schematic diagram of in-situ infiltration of rock for 3D printing in this invention;

[0032] Figure 4 This invention provides a flowchart of the in-situ infiltration process for 3D printing of rocks.

[0033] Forming cylinder 100; horizontal motion device 200; powder spreading device 300; printing and impregnation device 400; vertical motion device 101; guide column 102; forming substrate 103; X-direction motion module 201; Y-direction motion module 202; printing and impregnation device mounting bracket 203; powder spreading motion device 301; powder dropping cylinder 302; powder spreading roller 303; powder spreading motor 304; micro-droplet jetting device 401; binder ink cartridge 402; binder storage box 403; liquid extrusion device 404; air pressure regulating device 405. Detailed Implementation

[0034] The following embodiments further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0035] A schematic diagram of an apparatus for in-situ impregnation of rocks suitable for 3D printing according to the present invention is provided in the attached diagram. Figure 1 and attached Figure 2 As shown:

[0036] It consists of a forming cylinder 100, a horizontal motion device 200, a powder spreading device 300, and a printing and impregnation device 400.

[0037] The forming cylinder includes a vertical motion device 101, a guide post 102, and a forming substrate 103. The forming substrate 103 moves vertically under the drive of the vertical motion device 101. The forming sample is formed on the forming substrate 103, and the guide post 102 ensures the stability of the vertical movement.

[0038] The horizontal motion device includes an X-direction motion module 201, a Y-direction motion module 202, and a mounting bracket 203 for the printing and impregnation device. The X-direction motion module 201 and the Y-direction motion module 202 move in tandem, driving the printing and impregnation device 400 to move in the horizontal plane.

[0039] The powder spreading device 300 includes a powder spreading motion device 301, a powder dropping cylinder 302, a powder spreading roller 303, and a powder spreading motor 304. The powder spreading motion device 301 drives the powder spreading device 300 to move along the X direction. During the movement, the powder dropping cylinder 302 drops powder, and at the same time, the powder spreading motor 304 drives the powder spreading roller 303 to rotate, realizing the powder dropping, spreading, and leveling process on the forming surface.

[0040] The printing and impregnation apparatus 400 includes a droplet ejection device 401, an adhesive cartridge 402 and an adhesive storage container 403, a liquid extrusion device 404, and a pressure regulating device 405. The adhesive storage container 403 and the pressure regulating device 405 are fixed to the 3D printer and connected to the adhesive cartridge 402 and the liquid extrusion device 404 via hoses. A host computer sends a control signal to drive the droplet ejection device 401 to eject the adhesive, and the adhesive cartridge 402 and the adhesive storage container 403 supply the adhesive to the ejection device 401. The host computer also sends a control signal to drive the pressure regulating device 405, which uses high-pressure gas to drive the liquid extrusion device 404 to extrude the impregnation agent.

[0041] The specific implementation provides a method for preparing rock samples by in-situ infiltration through 3D printing, as shown in the attached figure. Figure 3 and attached Figure 4 As shown:

[0042] (1) Preparation of 3D printing powder: According to the proportion of sandstone mineral composition, quartz powder, feldspar powder, rock chips, clay powder and curing agent are mixed evenly according to the mass ratio.

[0043] Specifically, the quartz powder is a combination of large-particle-size powder (100-200 μm) and small-particle-size powder (10-50 μm). The feldspar powder is any one or a mixture of sodium feldspar, potassium feldspar, and calcium feldspar; the particle size range is 50-200 μm. The rock fragments are igneous rock fragments, and the clay powder is kaolinite, hydromica, etc. The curing agent is a non-volatile acidic catalyst such as toluenesulfonic acid in a furan resin system; the content of the curing agent accounts for 0.3%-1% of the mass of the 3D printing powder.

[0044] Specific mixing methods include, but are not limited to, planetary ball milling, stirring mixing, V-shaped mixing, and three-dimensional rotary mixing.

[0045] (2) Import the three-dimensional geometric model data of sandstone and the three-dimensional spatial distribution data of sandstone minerals into the 3D printer; input the 3D printing powder obtained in step 1 into the powder storage hopper of the 3D printer; the 3D printer conveys the 3D printing powder in the powder storage hopper to the forming plane through the powder feeding mechanism; the bottom plate of the forming cylinder descends a certain height along the Z axis according to the printing layer thickness parameters; the powder spreading device moves along the X or Y direction to complete the powder spreading.

[0046] Specifically, the powder input method employs either vacuum suction or belt-type powder feeding. The powder spreading process includes two steps: powder feeding and surface leveling. The powder feeding method uses either a bottom-feeding method based on the lifting of a powder feeding cylinder or an top-feeding method based on a powder drop hopper. Surface leveling is achieved using either a rotating powder spreading roller or a sliding scraper. The thickness of a single layer of powder spread ranges from 0.05 to 0.4 mm.

[0047] (3) The inkjet printhead moves along the X and Y directions according to the three-dimensional geometric model of sandstone to print the binder as needed, forming the geometric cross-sectional shape of the rock. The extrusion printhead moves along the X and Y directions according to the three-dimensional spatial distribution of sandstone mineral composition to print the impregnating agent as needed in the forming area, completing the single-layer impregnation of the rock, uniform impregnation, or impregnation of specific mineral components.

[0048] Specifically, the adhesive is a furan resin solution.

[0049] Specifically, the impregnating agent can be any one or a mixture of silicon-based, silicon-aluminum-based, and aluminum-based impregnating agents, depending on the chemical composition requirements of the rock sample. Silicon-based impregnating agents are liquid mineral binders that can be converted into silica, such as water glass, alkoxysilanes, and silica sols. Depending on the conversion mechanism of the impregnating agent, auxiliary heating and spraying devices are provided. Silicon-aluminum-based impregnating agents are liquid impregnating agents used to prepare silicon-aluminum gel systems. Water glass and any one or a mixture of alkoxysilanes are used as the silicon source for preparing silicon-aluminum gels, while aluminum sulfate, aluminum chloride, and aluminum hydroxide are used as the aluminum source. The two reagents are mixed and stirred evenly before being used in the silicon-aluminum-based impregnating agent. Aluminum-based impregnating agents include sol-gel aluminum impregnating agents (such as boehmite sol) and pyrolytic aluminum impregnating agents (such as ammonium aluminum sulfate, ammonium aluminum carbonate, and aluminum chloride).

[0050] (4) Repeat steps 2 and 3 to prepare in-situ infiltrated rock samples layer by layer.

[0051] (5) The printed rock sample is sintered at high temperature to complete the mineralization transformation of the impregnating agent and improve the strength of the sample; the high temperature sintering temperature is 1000~1400℃ and the sintering time is 12~24 hours.

[0052] In a specific embodiment, the sandstone powder preparation process is as follows:

[0053] (1) Based on the mineral composition ratio of sandstone, four mineral powders were initially mixed using a planetary ball mill at a mass ratio of quartz:feldspar:rock fragments:clay = 60:30:5:5. The quartz powder had particle sizes of 150 μm and 50 μm, the feldspar had a particle size of 50 μm, and the basalt rock fragments had a particle size of 50 μm. The purpose of selecting quartz powders of different particle sizes was to control the gradation relationship of the prepared sandstone 3D printing powder.

[0054] (2) Add 0.5 wt% toluenesulfonic acid curing agent to the uniformly mixed quartz sandstone powder, and ball mill the powder again. After ball milling, use a rotary vibrating sieve to remove large particles from the powder through a 100-mesh sieve to obtain 3D printing quartz sandstone powder.

[0055] The preparation processes for various types of impregnating agents in specific embodiments are as follows:

[0056] Silicon-based impregnating agent: A homogeneous solution of silicon-based impregnating liquid is obtained by mixing tetraethyl orthosilicate, deionized water, ethanol and acetic acid.

[0057] Silicon-aluminum impregnating agent: Water glass is dissolved in deionized water to prepare a saturated water glass solution; aluminum chloride is dissolved in water to prepare a 3 mol / L aluminum chloride solution. The two solutions are mixed and undergo a double hydrolysis reaction to produce aluminum silicate, which is used as a silicon-aluminum impregnating agent.

[0058] Aluminum-based impregnating agent: Aluminum isopropoxide is dissolved in deionized water, where it undergoes hydrolysis and polymerization. Nitric acid is then added to dissolve the precipitate again, yielding a boehmite sol solution, which is used as an aluminum-based impregnating agent.

[0059] Example 1

[0060] (1) The 3D printing sandstone powder is fed into the 3D printer through a vacuum feeder. The data file containing the rock geometry and internal mineral component distribution is imported into the 3D printer. The printing layer thickness is set to 0.15mm, the powder feeding mechanism moving speed is set to 250mm / s, and the powder feeding belt speed is set to 200mm / s.

[0061] (2) Start the printing program. The powder feeding mechanism, consisting of a powder feeding belt and a powder spreading roller, moves along the X-axis. During the movement of the mechanism, the powder feeding belt spreads the 3D printing powder evenly at a preset speed, while the powder spreading roller rotates to complete one layer of powder spreading.

[0062] (3) The inkjet printhead 1 moves to the designated position according to the rock geometry within the layer. The piezoelectric module inside the printhead is driven by a pulse signal to complete the spraying of furan resin binder at the required position. Toluenesulfonic acid curing agent and furan resin react and cure.

[0063] (4) The extrusion printhead 2, according to the requirements of the in-situ impregnation process, extrudes a silica sol impregnating agent with a particle size of 50-100nm through a plunger, and the forming area overlaps with the working area of ​​the inkjet printhead. After the silica sol is extruded, the in-situ impregnation process within this layer is completed.

[0064] (5) Move the auxiliary electric heating plate above the forming surface, control the baking temperature to 80℃, bake for 15 minutes, and complete the initial coagulation of the silica sol impregnation liquid.

[0065] (6) If it is necessary to further increase the impregnation concentration, the above steps (4) to (5) can be repeated until the impregnation process requirements are met.

[0066] (7) The substrate is lowered by 0.15 mm to complete the printing, in-situ impregnation, and preliminary solidification process of the forming layer.

[0067] (8) Repeat steps (3) to (7) above to complete the 3D printing and in-situ infiltration and consolidation of the entire quartz sandstone.

[0068] (9) The printed rock sample is sintered at high temperature to complete the mineralization transformation of the impregnating agent and improve the strength of the sample; the high temperature sintering temperature is 1200℃ and the sintering time is 12 hours.

[0069] Example 2:

[0070] (1) The 3D printing powder is fed into the 3D printer through a belt feeder. The data file containing the rock geometry and internal mineral component distribution is imported into the 3D printer. The printing layer thickness is set to 0.1mm, the powder feeding mechanism moving speed is set to 300mm / s, and the powder feeding belt speed is set to 250mm / s.

[0071] (2) Start the printing program. The powder feeding mechanism, consisting of a powder feeding belt and a powder spreading roller, moves along the X-axis. During the movement of the mechanism, the powder feeding belt spreads the 3D printing powder evenly at a preset speed, while the powder spreading roller rotates to complete one layer of powder spreading.

[0072] (3) The inkjet printhead moves to the designated position according to the rock geometry within the layer, and the furan resin binder is sprayed at the desired position by electric heating and foaming drive inside the printhead. Toluenesulfonic acid curing agent and furan resin binder react and cure.

[0073] (4) Extrusion printhead 1 According to the requirements of the in-situ impregnation process, water glass solution and aluminum chloride solution are pneumatically extruded. The forming area overlaps with the working area of ​​the inkjet printhead. The two react to produce orthosilicic acid and aluminum hydroxide, thus completing the in-situ impregnation process in this layer.

[0074] (5) Move the auxiliary electric heating plate above the forming surface, control the baking temperature to 190℃, bake for 15 minutes, and complete the preliminary aluminum hydroxide consolidation process.

[0075] (6) The extrusion printhead 2 moves to the designated position according to the distribution data of the mineral components in the layer. The forming area only covers the area where the content of the specified mineral components needs to be increased. The required silicon-based, silicon-aluminum-based or aluminum-based impregnating agent is extruded by pneumatic extrusion to increase the concentration of silica or alumina minerals in the area and complete the mineral component control process in the layer.

[0076] (7) If it is necessary to further increase the infiltration concentration or adjust the mineral composition, the above steps (3) to (6) can be repeated until the infiltration and mineral composition adjustment process requirements are met.

[0077] (8) The substrate is lowered by 0.15 mm to complete the printing, in-situ impregnation, and preliminary solidification process of the forming layer.

[0078] (9) Repeat steps (3) to (8) above to complete the entire sandstone 3D printing, in-situ infiltration and consolidation process.

[0079] (10) The printed rock sample is sintered at high temperature to complete the mineralization transformation of the impregnating agent and improve the strength of the sample; the high temperature sintering temperature is 1000℃ and the sintering time is 20 hours.

Claims

1. A method for in-situ infiltration of rock in 3D printing, characterized in that... Includes the following steps: (1) According to the proportion of sandstone mineral composition, quartz powder, feldspar powder, rock fragment powder, clay powder and curing agent are mixed evenly; the curing agent is toluenesulfonic acid, and the amount used accounts for 0.3% to 1% of the total mass of the powder; (2) Powder bed 3D printing technology is used to complete the powder spreading on the printing surface; (3) Based on the three-dimensional geometric model of sandstone, inkjet print the adhesive on the printing surface to form the cross-sectional shape of the rock sample; The inkjet printing binder is produced using a microdroplet ejection method based on pressure point drive or heat drive, and the binder is a furan resin solution; The impregnating agent is extruded and printed on the printing surface according to the three-dimensional spatial distribution of sandstone mineral composition, so as to meet the requirements of chemical composition and strength of different parts of rock sample on a single cross section. The extruded printing impregnating agent adopts micro-droplet spray or liquid extrusion. The impregnating agent adopts any one or a mixture of silicon-based impregnating agent, silicon-aluminum-based impregnating agent, and aluminum-based impregnating agent according to the chemical composition requirements of rock sample. The silicon-based impregnating agent is any one of water glass, alkoxysilane, and silica sol; The silicon-aluminum impregnating agent is a silicon-aluminum gel system; wherein any one or a mixture of water glass and alkoxysilane is used as the silicon source for preparing silicon-aluminum gel; any one or a mixture of aluminum sulfate, aluminum chloride, and aluminum hydroxide is used as the aluminum source for preparing silicon-aluminum gel; the silicon source and the aluminum source are blended to obtain the silicon-aluminum impregnating agent. The aluminum-based impregnating agent is a sol-gel aluminum impregnating agent or a pyrolytic aluminum impregnating agent; specifically, it is any one of boehmite sol, ammonium aluminum sulfate, ammonium aluminum carbonate, and aluminum chloride. (4) Repeat step (3) to prepare in-situ infiltrated rock samples layer by layer; (5) The printed rock sample is sintered at high temperature to complete the mineralization transformation of the impregnating agent and improve the strength of the sample.

2. The in-situ infiltration method for 3D printing of rocks as described in claim 1, characterized in that... The quartz powder mentioned in step (1) is a mixture of large-particle-size powder of 100 ~ 200 μm and small-particle-size powder of 10 ~ 50 μm; the mass ratio of the two quartz powders is 9:1, 8:2, 7:3 or 6:4 according to the powder gradation relationship.

3. The in-situ infiltration method for 3D printing of rocks as described in claim 1, characterized in that... The feldspar powder mentioned in step (1) is any one or a mixture of sodium feldspar, potassium feldspar, and calcium feldspar; the particle size range is 50 ~ 200 μm.

4. The in-situ infiltration method for 3D printing of rocks as described in claim 1, characterized in that... The rock fragments in step (1) are igneous rock fragments; the clay powder is kaolinite or hydromica; the particle size range is 2~20μm.

5. The in-situ infiltration method for 3D printing of rock as described in claim 1, characterized in that... Step (2) uses vacuum suction or powder feeding belt to transport the mixed raw material from step (1) to the 3D printer; the powder spreading process includes two steps: powder feeding and surface leveling. The powder feeding method is either a bottom powder feeding method based on the lifting of the powder feeding cylinder or an top powder feeding method based on the powder dropping hopper; the surface leveling is achieved by rotating the powder spreading roller or moving the scraper.

6. The in-situ infiltration method for rock 3D printing as described in claim 1, characterized in that... Step (2) The thickness of a single layer of powder is 0.05~0.4mm.

7. The in-situ infiltration method for 3D printing of rocks as described in claim 1, characterized in that... Step (5) The high-temperature sintering temperature is 1000~1400℃ and the sintering time is 12~24 hours.

Citation Information

Patent Citations

  • Sand mold printing device for rock sample

    CN116809870A

  • 3D printing geopolymer for complex rock mass physical model and using method of 3D printing geopolymer

    CN112028551A

  • Complex structure geologic model preparation method based on lithofacies distribution

    CN116448514A